The famine exposure in early life and metabolic syndrome in adulthood. Issue 1 (February 2017) - Wang, Ningjian; Wang, Xiaojin; Li, Qin; Han, Bing; Chen, Yi; Zhu, Chunfang; Chen, Yingchao; Lin, Dongping; Wang, Bingshun; Jensen, Michael D.; Lu, Yingli
Summary: Background & aims: Epidemiologic studies have revealed that early-life conditions influence later risk of chronic diseases. We aimed to explore whether exposure to Chinese famine between 1959 and 1962 during fetal and childhood period was related with metabolic syndrome (MS) in adulthood. Methods: 6445 subjects from SPECT-China study were divided into fetal-exposed (1959–1962), childhood-exposed (1949–1958), adolescence/young adult-exposed (1921–1948), non-exposed (1963–1974) and non-exposed (after 1975). MS was defined by the International Diabetes Federation criteria. Results: The prevalences of MS in the non-exposed (1963–1974), fetal and childhood-exposed were 16.4%, 20.1% and 19.1% in men and 13.5%, 23.7% and 33.5% in women, respectively. After adjustment for age, compared with non-exposed (1963–1974), fetal and childhood-exposed women had significantly higher prevalences of MS ( P  < 0.05), but not in men. Famine exposure during the fetal period (OR 1.47, 95% CI 1.05, 2.07) and childhood (OR 1.80, 95% CI 1.22, 2.67) was associated with higher risk of MS in women after adjusting for age (both P  < 0.05). Further adjustments for age, smoking, rural/urban residence and economic status did not significantly attenuate this association. Conclusions: Exposure to famine in early life had sex-specific association with MS. It also suggests the adverse effects of malnutrition might extend beyond the 'first 1000 days' and last 9 years. Highlights: Exposure to famine in early life had sex-specific association with metabolic syndrome. Women were more prone to be associated with metabolic syndrome when exposed to famine during fetus and childhood period. The adverse effects of undernutrition might extend beyond the 'first 1000 days'.